A text-based learning model for college General English - Christina Eli Indriyani (Universitas Katolik Indonesia Atma Jaya, 2018)
The fact that an English learning program is provided to equip college students with English skills poses several problems since every university, even every non-English department, likely has its own system. One solution is to provide an acceptable material that is arranged based on the language that needs to be acquired. In order to solve the problem of supporting the English learning process in college, this research aims to produce a learning model for the novice level, i.e. college general English. The general English course is needed to provide the students with college English before academic English. Thus, the problem discussed in this study is what is the acceptable product of the text-based college general English? The researcher employed ADDIE model for the instructional design. The researcher also adopted Borg’s and Gall’s R&D model as the research methodology. The final result was a course book named College Just Ahead. This book consists of five units, which has two or three sub-units in every unit. The result showed that the product was acceptable by the mean score above 4.00 out of 5. Therefore, when it is completed, the course is more transferable. The students and instructors more focus on the process of acquiring an English competence, so that the product is more valid and reliable.